2020
DOI: 10.1101/2020.12.16.20248345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived stress by students of the medical sciences in Cuba toward the COVID-19 pandemic: results of an online survey

Abstract: IntroductionThe aims of this study were to determine the usefulness of the Modified (10-items) Scale of Perceived Stress related to COVID-19 (EEP-10-C by its acronym in Spanish) and to identify the levels of stress perceived by students of the medical sciences in Cuba toward the COVID-19 pandemic.MethodsA cross-sectional study was conducted, with self-reported data of students from fourteen Cuban Universities of Medical Sciences (n = 200), through an online survey. The EEP-10-C was used as an instrument to ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…An online survey of approximately 20 min was conducted between 21 September and 26 October 2020 while the international student campuses were still in lockdown. The survey collected (i) demographic information, (ii) qualitative data on challenges faced and coping strategies and achievements throughout the lockdown, and (iii) quantitative data on perceived stress levels, the latter by utilising Cohen’s Short Form of Perceived Stress Scale (PSS-10) [ 31 ] adapted for the COVID-19 lockdown event [ 25 , 28 , 32 ]. Cohen’s PSS-10 instrument enjoys wide and enduring usage as an instrument for measuring perceived stress levels and reports on situations of daily life, which are considered as stressful (in this research specified as lockdown and isolation due to the outbreak of COVID-19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An online survey of approximately 20 min was conducted between 21 September and 26 October 2020 while the international student campuses were still in lockdown. The survey collected (i) demographic information, (ii) qualitative data on challenges faced and coping strategies and achievements throughout the lockdown, and (iii) quantitative data on perceived stress levels, the latter by utilising Cohen’s Short Form of Perceived Stress Scale (PSS-10) [ 31 ] adapted for the COVID-19 lockdown event [ 25 , 28 , 32 ]. Cohen’s PSS-10 instrument enjoys wide and enduring usage as an instrument for measuring perceived stress levels and reports on situations of daily life, which are considered as stressful (in this research specified as lockdown and isolation due to the outbreak of COVID-19).…”
Section: Methodsmentioning
confidence: 99%
“…Answers were scored as follows: 0—never; 1—almost never; 2—sometimes; 3—fairly often; and 4—very often. Participant total scores on the PSS-10 can range from 0 to 40, with higher scores indicating higher perceived stress (see results below in the Descriptive Statistics of Perceived Levels of Stress) [ 17 , 23 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 The instrument's relevance is evidenced by several citations of using the PSS-C-10 in the world context. [3][4][5] The PSS-10-C presented a one-dimensional structure, without a confirmatory analysis factorial, and high internal consistency; however, the need to make adjustments in PSS-10-C was noted. 1 Since perspective focused on the writing of the items, a review of the PSS-10-C suggested that the Spanish item 6 ('I have felt unable to face the things I have to do to control the possible infection') could partly explain that the factorial solution was not wholly satisfactory in explaining less than 50% of the variance.…”
Section: To the Editormentioning
confidence: 99%